Empirical calibration of uranium releases in the terrestrial environment of nuclear fuel cycle facilities. (May 2017) - Pourcelot, Laurent; Masson, Olivier; Saey, Lionel; Conil, Sébastien; Boulet, Béatrice; Cariou, Nicolas
Abstract: In the present paper the activity of uranium isotopes measured in plants and aerosols taken downwind of the releases of three nuclear fuel settlements was compared between them and with the activity measured at remote sites. An enhancement of 238 U activity as well as 235 U/ 238 U anomalies and 236 U are noticeable in wheat, grass, tree leaves and aerosols taken at the edge of nuclear fuel settlements, which show the influence of uranium chronic releases. Further plants taken at the edge of the studied sites and a few published data acquired in the same experimental conditions show that the 238 U activity in plants is influenced by the intensity of the U atmospheric releases. Assuming that 238 U in plant is proportional to the intensity of the releases, we proposed empirical relationships which allow to characterize the chronic releases on the ground. Other sources of U contamination in plants such as accidental releases and "delayed source" of uranium in soil are also discussed in the light of uranium isotopes signatures. Highlights: Plants and aerosols were taken downwind of the release from fuel facilities. Samples exhibit U isotopes anomalies (U enhancement, 235 U/ 238 U anomalies and 236 U). An empirical relationship between U in plants and the release intensity is derived. Other sources of U are also involved: accidental releases and contaminated soils.